Flora illustrata : great works from the LuEsther T. Mertz Library of the New York Botanical Garden - New York Botanical Garden; Fraser, Susan M.; Sellers, Vanessa Bezemer; New York Botanical Garden; Yale University Press (Bronx, New York : The New York Botanical Garden ; New Haven ; London : Yale University Press, 2014)
The renowned LuEsther T. Mertz Library of The New York Botanical Garden counts among its holdings many of the most beautiful and pioneering botanical and horticultural works ever created. More than eight centuries of knowledge, from the twelfth century to the present, are represented in the library's collection of over one million items. In this sumptuously illustrated volume, international experts introduce us to some of the library's most fascinating works--exceedingly rare books, stunning botanical artworks, handwritten manuscripts, Renaissance herbals, nursery catalogs, explorers' notebooks, and more. The contributors hold these treasures up for close inspection and offer surprising insights into their histories and importance.
Noble science : building the library collection / Susan M. Fraser --European medieval and Renaissance herbals / Lucia Tongiorgi Tomasi --"Plants in their perfection" : the botanical garden and the illustrated book / Therese O'Malley --Pleasure gardens in print : recreation and education in the landscape, 1550-1850 / Vanessa Bezemer Sellers --Linnaeus and the foundation of modern botany / Gina Douglas --New World explorations : Brazil / H. Walter Lack --Creating a North American flora / Elizabeth S. Eustis with David Andrews --Early American horticultural traditions : gardening with plants from the New World / Mark Laird --Toward an American landscape theory / Judith K. Major --The horticultural enterprise : markets, mail, and media in nineteenth-century America / Elizabeth S. Eustis --"An American Kew" / Elizabeth Barlow Rogers.
Includes bibliographical references (pages 283-288) and index.
Keywords: LuEsther T. Mertz Library -- Catalogs; LuEsther T. Mertz Library -- History; Botanical libraries -- New York (State) -- New York; Book collecting -- New York (State) -- New York; Botany -- Bibliography -- Catalogs; Horticulture -- Bibliography -- Catalogs; Botanical illustration -- Bibliography -- Catalogs; Illustrated books -- Bibliography -- Catalogs; Rare books -- Bibliography -- Catalogs